THE EFFECT OF STRUCTURED PHYSICAL EXERCISE ON OVERALL SURVIVAL IN ADVANCED GASTROINTESTINAL CANCER PATIENTS WITH CACHEXIA: A CRITICAL REVIEW AND METHODOLOGICAL ANALYSIS ONGOING RCT PROTOCOLS - Eunike Gracia Sigalingging; Ida Bagus Aditya Nugraha (Journal of Innovative and Creativity, 2026)
Cachexia in patients with advanced gastrointestinal (GI) cancer significantly impairs overall survival (OS) and quality of life, but definitive evidence from randomized controlled trials (RCTs) on structured physical exercise (SPE) is scarce. This evidence-based clinical review (EBCR) aimed to assess the methodological quality and clinical relevance of ongoing RCT protocols (RELEVIUM, BiCyCLE NMES, REBUILD) using the Cochrane RoB 2.0 and the Oxford CEBM criteria. This systematic literature review with critical narrative synthesis employed a mixed-methods approach, targeting adult patients with advanced GI cancer with cachexia/sarcopenia (PICO framework). The sample consisted of three protocols (N=200, 120, 94) from 221 screened articles (PubMed, Cochrane, Google Scholar; November 2025). Instruments included the PICO search strategy, RoB 2.0 (five domains), and a qualitative synthesis tool. Data were analyzed using narrative comparison and risk of bias assessment without meta-analysis. Results showed a high risk of blinding bias in two protocols, OS was only listed as a secondary outcome in BiCyCLE NMES, and heterogeneity in LBM measurements (CT scan vs. BIA). In conclusion, promising designs at Level 1b evidence exist, but methodological gaps limit OS comparability; OS/CT scan standardization is recommended.